Research on Soundscape Design Strategies for Public Spaces in Dong Village, Dali - Li, Jiaqun (Transactions on Social Science, Education and Humanities Research, 2024)
Soundscape reflects the ecological, cultural and social characteristics of regions and ethnic groups and is an important part of the public environment. Because in the past environmental design, the breadth and depth of the design that considers the human settlement environment system as a large framework should be included and involved. Therefore, this article analyzes the existing public space and landscape nodes of the public environment of Dali Dong Village, and uses the knowledge of environmental science, sociology, landscape science and other related disciplines to explore the Dong village public environment as the design practice object. It hopes to provide a useful reference for the research on sound landscape design of traditional ethnic minority settlements in my country.